Aspectos do processo de medição em mecânica quântica: detectores imperfeitos e Efeito Zenão Quântico - Romeu Rossi Junior (2008)
We investigate some effects related to quantum measurement process. We study a theoretical model for atomic detections in microwave cavity experiments. The model allows for the introduction of empirical imperfections in the analysis of experiments in this system. Two investigations on foundations of Quantum Zeno Effect are presented. Thefirst one consists in experimental proposals for the effect observation in a bipartite system. Empirical limitations are made explicit. In the second investigation, we show that the Quantum Zeno Effect prevails even if the measurements are not complete. Finally we present a protocol which allows for the quantum evolution control through a single auxiliary system.